Gestão documental em prontuários médicos: o programa Estratégia Saúde da Família - ESF - SILVA, Maria de Fátima Siqueira da (2018)
This study has the objective of proposing archival recommendations for standardized records management at primary clinics and their Family Health Strategies (FHS) program in the municipality of Ananindeua, analyze documentation storage and justify the need for a professional archivist, training of health care professionals responsible for records archival, and evaluating physical condition and resources. This empirical study was developed using quantitative and qualitative methods. Theoretical background was based on literature review and evaluation of documentation management and medical records. The work was done in loco through interviews and analysis of photographs. The results show that despite the organizational efforts by archival workers, the lack of standardized records management at FHS’s is evident by the lack of a singular pattern that follow norms of archival practices. Thus, proposing recommendations for adequate archival patronization at primary health clinics.